Impact of pesticide on the physical and chemical agricultural soil in a semi-arid region of Algeria (M’Sila) - Bensaci, Ettayib; Bakhti, Fatima Zahra; Zouggaghe, Fatah (Future Science, 2026)
This study aims to monitor the impacts of pesticides on the physical and chemical quality of agricultural soil in Algeria's semi-arid region. The region primarily cultivates market garden crops such as potatoes and wheat. Sandy soil types and a semi-arid climate characterize it. Twenty- seven samples were collected from various soil horizons at different depths and locations within the study area. Among these, 9 samples were designated as controls, 9 were treated with a potent herbicide called haloxyfop-methyl ester, and the remaining 9 were treated with a fungicide containing two active ingredients: fenamidone and a methyl ester. The measured parameters (pH, conductivity, TDS, CO, MO, lime- stone, Mg+, Ca+, NO2, P2O5, K2O) exhibited variability, with the treated samples generally showing higher values than the control samples. This difference can be attributed to various factors, such as treatment con- ditions, characteristics of the study area, types of pesticides used, and the application of mineral and organic fertilizers, as well as chemical pesticides. Intensive agriculture often employs this approach, aiming to produce large quantities of food on a relatively small land area. The heavy metals analysis (iron, copper, manganese, aluminum, and chro- mium) of agricultural soil showed concentration values within interna- tional norms. Despite this, these metals remain toxic chemicals with bi- oaccumulative persistence in the environment. The uncontrolled use of pesticides impacts both the short-term and long-term soil quality. While they effectively kill weeds and fungi, they also penetrate and ac- cumulate in the soil and pollute groundwater. It is crucial to use herbi- cides sparingly and choose those with minimal environmental impact.